La FormaciÃ³n Investigativa Como Salida Para El Compromiso Profesional De Futuros Profesores En Angola - Figueiredo, D. Eugenio; Montoro, Miriam Agreda; Lucena, MarÃa Angustias Hinojo (European Scientific Journal, ESJ, 2016)
This paper aims to enhance the research carried out on teacher training as a current need in Angolaâ€™s Higher Education due to the lack of any practical introduction to research as part of an essential mode of action in professional training. This paper uses references provided in social sciences as a basis to inform about the importance of research training during the educational process of both students and teachers in Angola.. We conclude there is a need to propose policies that create profound changes in the training model of education practitioners so as to include an efficient general knowledge as well as the ability to develop proper research.